Characterization of the Sexually Dimorphic fruitless Neurons That Regulate Copulation Duration - Jois, Shreyas; Chan, Yick Bun; Fernandez, Maria Paz; Leung, Adelaine Kwun-Wai (Frontiers in Physiology, 2018)
Male courtship in Drosophila melanogaster is a sexually dimorphic innate behavior that is hardwired in the nervous system. Understanding the neural mechanism of courtship behavior requires the anatomical and functional characterization of all the neurons involved. Courtship involves a series of distinctive behavioral patterns, culminating in the final copulation step, where sperm from the male are transferred to the female. The duration of this process is tightly controlled by multiple genes. The fruitless (fru) gene is one of the factors that regulate the duration of copulation. Using several intersectional genetic combinations to restrict the labeling of GAL4 lines, we found that a subset of a serotonergic cluster of fru neurons co-express the dopamine-synthesizing enzyme, tyrosine hydroxylase, and provide behavioral and immunological evidence that these neurons are involved in the regulation of copulation duration.